Principles of corporate finance : study guide - Levy, Haim. (Cincinnati, OH : South-Western College, 1998)
This book is divided into seven parts: The financial environment; Project evaluation; Portfolio and capital budget decisions; Long-term financing; Capital structure and dividend policy; Financial Planning; and Shoort-Term financial management.
Keywords: Finance; Business enterprises; Corporations; Corporations -- Finance -- Problems, exercises, etc